2016
DOI: 10.5194/angeo-34-543-2016
|View full text |Cite
|
Sign up to set email alerts
|

Properties of inertia-gravity waves in the lowermost stratosphere as observed by the PANSY radar over Syowa Station in the Antarctic

Abstract: Abstract. Inertia-gravity waves (IGWs) are an important component for the dynamics of the middle atmosphere. However, observational studies needed to constrain their forcing are still insufficient especially in the remote areas of the Antarctic region. One year of observational data (January to December 2013) by the PANSY radar of the wind components (vertical resolution of 150 m and temporal resolution of 30 min) are used to derive statistical analysis of the properties of IGWs with short vertical wavelengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…GW observations have been performed in the lower, middle, and upper atmospheres of the Antarctic by satellites [ Baumgaertner and McDonald , ; Alexander et al ., ; Liu et al ., ], in situ (i.e., radiosondes [ Allen and Vincent , ; Yoshiki and Sato , ]), and by ground‐based instruments (i.e., lidars [ Yamashita et al ., ; Alexander et al ., ; Chen et al ., ; Kaifler et al ., ; Lu et al ., ; Chen et al ., ; Zhao et al ., ] and radars [ Dowdy et al ., ; Shibuya et al ., ; Mihalikova et al ., ]). However, most of these observations have a limited range of observable height.…”
Section: Introductionmentioning
confidence: 99%
“…GW observations have been performed in the lower, middle, and upper atmospheres of the Antarctic by satellites [ Baumgaertner and McDonald , ; Alexander et al ., ; Liu et al ., ], in situ (i.e., radiosondes [ Allen and Vincent , ; Yoshiki and Sato , ]), and by ground‐based instruments (i.e., lidars [ Yamashita et al ., ; Alexander et al ., ; Chen et al ., ; Kaifler et al ., ; Lu et al ., ; Chen et al ., ; Zhao et al ., ] and radars [ Dowdy et al ., ; Shibuya et al ., ; Mihalikova et al ., ]). However, most of these observations have a limited range of observable height.…”
Section: Introductionmentioning
confidence: 99%
“…A plausible generation mechanism of inertia-gravity waves in the upper stratosphere is spontaneous radiation from the polar night jet (e.g., Sato and Yoshiki, 2008). It is also worth noting that observational studies show high percentages of downward gravity wave propagation in the polar stratosphere compared to those found at low and middle latitudes (e.g., Yoshiki and Sato, 2000;Guest et al, 2000;Moffat-Griffin et al, 2013;Murphy et al, 2014;Mihalikova et al, 2016). To confirm this possibility, we examined fluctuation characteristics and background zonal winds of the upper stratosphere.…”
Section: Wave Propagation and Generation Mechanismmentioning
confidence: 98%
“…Based on profiles of wind and temperature from radiosonde and radar observations, hodograph method derived from the IGW polarization equation is extensively applied to analyze IGW propagation (Huang et al, ; Nath et al, ; Mihalikova et al, ; Moffat‐Griffin et al, , ; Ratnam et al, ; Vincent & Alexander, ; Wang et al, ; Zhang & Yi, , ). In particular, when a large‐amplitude IGW propagates in a background field with weak shear and slow temporal variation, hodograph method is regarded as an accurate technique.…”
Section: Extraction Of Quasi Monochromatic Igwmentioning
confidence: 99%
“…For example, sheared wind field causes not only energy exchange between GWs and the background flow by means of the work due to Reynolds stress but also GW filtering or reflection phenomenon due to the Doppler effect (Hines, ; Huang et al, , ; Walterscheid, ). In the past several decades, a large number of studies revealed the geographical and seasonal variability of GW source, propagation, structure, and spectrum based on radiosonde (Nath et al, , ; Pfenninger et al, ; Vincent & Alexander, ; Wang et al, ; Yoshiki & Sato, ; Zhang & Yi, , ; Zhang et al, ), radar (Mihalikova et al, ; Nastrom & Eaton, ; Ratnam et al, ; Riggin et al, , ; Sato et al, ), lidar (Alexander et al, ; Hu et al, ; Huang et al, ; B. Kaifler et al, ; T. Li et al, ; Lu et al, ; Wilson et al, ; Xu et al, ; Yuan et al, ), airglow imager (Hickey et al, ; Hickey et al, ; Z . Li et al, ; Nielsen et al, ; Snively et al, ; Swenson & Mende, ; Yue et al, , ), rocketsonde (Eckermann et al, ; Hamilton, ), and satellite (Alexander et al, ; Alexander & Rosenlof, ; Ern et al, ; Wright et al, ; Wu & Waters, ; Yamashita et al, ) measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation